Melanoma with gastric metastases - Katherine Wong; Sam W. Serafi; Abhijit S. Bhatia; Irene Ibarra; Elizabeth A. Allen (Greater Baltimore Medical Center, 2016)
An 81-year-old woman with a history of malignant melanoma who presented with dyspnea and fatigue was found to have metastases to the stomach detected on endoscopy. Primary cutaneous malignant melanoma with gastric metastases is a rare occurrence, and it is often not detected until autopsy because of its non-specific manifestations.